Active CO2 reservoir management for sustainable geothermal energy extraction and reduced leakage. Issue 1 (12th February 2013) - Elliot, Thomas R.; Buscheck, Thomas A.; Celia, Michael
Abstract Subsurface storage space is gaining recognition as a commodity for industrial and energy recovery operations. Geologic carbon dioxide (CO2) sequestration (GCS), wherein supercritical CO2 is injected into subsurface storage space, is under broad development in sedimentary reservoirs – particularly for hydrocarbon production, which uses supercritical CO2 as part of a carbon capture utilization and sequestration (CCUS) scheme. A novel CCUS operation is presented whereby we investigate the staged deployment of a coupled geothermal energy extraction (GEE)‐GCS operation in geothermal sedimentary reservoirs that re‐circulates extracted fluids. We identify sedimentary resources of the continental USA that have significant temperature at depths suitable for GCS. To predict the impact of a GEE‐GCS operation, a reservoir‐scale semi‐analytical model is used to simulate brine and CO2 migration through existing leakage pathways. With the goal of integrating GEE and GCS, a well‐site design exercise is undertaken, where we develop an idealized configuration for CO2 and brine production/reinjection wells. Results show potential geothermal sedimentary reservoirs suitable for GEE deployment exist in the continental USA; however the characteristics of each site should be investigated through a first stage GEE‐operation to determine GCS capacity. Our active CO2 reservoir management simulations demonstrate a decrease in injection and reservoir overpressures, a reduced migration of CO2 within the reservoir during active injection/extraction, and a reduced risk of brine and CO2 migration. With the use of the developed concentric‐ring well pattern, we demonstrate the longevity of thermal productivity from an ideal GEE site, while providing sufficient CO2 storage volume and trapping to act as a sequestration operation. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd